2015 International Conference on Distributed Computing in Sensor Systems 2015
DOI: 10.1109/dcoss.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Despeckling Efficiency of DCT-Based Filters Applied to SAR Images

Abstract: This paper deals with one way to predict efficiency of despeckling for images acquired by a single-or multi-look synthetic aperture radar (SAR). A particular filter based on discrete cosine transform (DCT) and adapted to speckle characteristics is considered. Two quantitative criteria characterizing despeckling efficiency are analyzed. It is shown that even one parameter that can be calculated for image blocks sequentially or in parallel allows carrying out a rather accurate prediction. Moreover, such a predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…An obvious tendency is that mean P 0.5σ becomes larger and IPSNR increases for smaller number of looks. Other conclusions that can be drawn from analysis in a study in [57] are the following. Prediction is possible for filtering techniques with and without VST, where the prediction quality is better in the latter case.…”
Section: Analysis For Signal-dependent and Spatially Correlated Typesmentioning
confidence: 98%
See 2 more Smart Citations
“…An obvious tendency is that mean P 0.5σ becomes larger and IPSNR increases for smaller number of looks. Other conclusions that can be drawn from analysis in a study in [57] are the following. Prediction is possible for filtering techniques with and without VST, where the prediction quality is better in the latter case.…”
Section: Analysis For Signal-dependent and Spatially Correlated Typesmentioning
confidence: 98%
“…They fit the curve well and have the arguments close to the maximal potential limit (0.38), where IPSNR attains very large values (approximately 10 dB and more). Additional studies concentrated on the multi-look SAR images that were corrupted by pure multiplicative noise [57]. Analysis has been done for speckle variance σ μ…”
Section: Analysis For Signal-dependent and Spatially Correlated Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…and I f kij ,i ¼ 1, …,I;j ¼ 1, …,J;k ¼ 1, …,K is the kth component image after despeckling or improvement of PSNR (IPSNR) equal to 10 log 10 σ 2 eq k =MSE out k [35,36]. Experiments carried out with 512Â512 pixel fragments of Sentinel SAR images have shown that IPSNR for Filter 1 varies within the limits from 5 to 12 dB, i.e., images enhance sufficiently.…”
Section: Filters and Their Impacts On Imagesmentioning
confidence: 99%
“…Note, that IMSSIM less than 0.005 or IPSNR-HVS-M smaller than 0.5 dB practically cannot be considered as a visual quality improvement. 37 Secondly, it has been shown in Refs. 26 and 51 that IPSNR about 3 dB is not recognized as e±cient denoising if noise in original images is intensive.…”
Section: New Solutions For Prediction Of Denoising E±ciency Indicatorsmentioning
confidence: 99%